PENGEMBANGAN E-LKPD BERBASIS PROBLEM BASED LEARNING (PBL) PADA MATA PELAJARAN PENDIDIKAN PANCASILA - Nst, Yeni; Fransaygu, Ronald; Ayudia, Inge (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The limited use of digital teaching materials and student’ low ability to express opinions and solve contextual problems in Pancasila Education learning require innovative learning resources. This study aimed to develop a Problem Based Learning (PBL)-based Electronic Student Worksheet (E-LKPD) for fourth-grade students in Pancasila Education, determine its validaty, and evaluate its practicality. The study employed a Research and Development (R&D) approach using the ADDIE development model, which consisted of the analysis, design, development, implementation, and evaluation stages. However, the research was limited to product development, expert validation, and practicality testing. The research subjects were fourth-grade students of SDN 1 Meurandeh. Data were collected throught interviews, observations, validation sheets completed by material, language, and media experts, as well as teacher and student response questionnaires. The result indicated that the developed PBL-based E-LKPD met the criteria of being highly valid based on expert validation and highly practical based on teacher and studens reponses. The product integrates the five syntax stages of Problem Based Learning into each learning activity, enabling students to participate actively in solving contextual problems related to mutual cooperation. Therefore, the developed E-LKPD is considered appropriate for supporting Pancasila Education learning in elementary schools.